2023
DOI: 10.3389/fpsyg.2023.1207569
|View full text |Cite
|
Sign up to set email alerts
|

Parental burnout, depression and emotional development of the preschoolers

Abstract: IntroductionParental burnout is becoming more and more prevalent in the world, mainly incultures with high demands towards parents. Parental burnout is distinctive from depression and might have its unique influence on child development, which isunder current international research. This work contributes to the understanding of parental burnout, maternal depression and child emotional development(specifically emotion comprehension) interrelations. Additionally, we explored whether there are differences in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Thus, although convincing evidence suggests that maternal depressive symptoms, specifically their intensity and duration, present risks for their children's health and development, the exact effects of PPD on the socioemotional child development are still poorly investigated. In Russia, on the contrary, a recent study with a modest sample size (n = 251) that focused on emotional development in preschoolers found no significant association with maternal depression at a child's mean age of 4.92 [17]. However, although the studies have consistently indicated a high prevalence of PPD ranging between 25% and 46% [18][19][20], to date there have been no longitudinal studies that examined the long-term impact of PPD, maternal depression during the early years and the depressive symptom trajectories on child socioemotional development.…”
Section: Introductionmentioning
confidence: 84%
“…Thus, although convincing evidence suggests that maternal depressive symptoms, specifically their intensity and duration, present risks for their children's health and development, the exact effects of PPD on the socioemotional child development are still poorly investigated. In Russia, on the contrary, a recent study with a modest sample size (n = 251) that focused on emotional development in preschoolers found no significant association with maternal depression at a child's mean age of 4.92 [17]. However, although the studies have consistently indicated a high prevalence of PPD ranging between 25% and 46% [18][19][20], to date there have been no longitudinal studies that examined the long-term impact of PPD, maternal depression during the early years and the depressive symptom trajectories on child socioemotional development.…”
Section: Introductionmentioning
confidence: 84%